A selective CO2 capture adsorbent and its preparation and application

Through the LTA-type zeolite molecular sieve material after sodium ion or potassium ion exchange, the problem of low partial pressure carbon dioxide separation efficiency is solved, and efficient carbon dioxide adsorption and separation is achieved, which is suitable for carbon dioxide capture in the mixed gas.

CN116135300BActive Publication Date: 2024-12-13CITY UNIV OF HONG KONG SHENZHEN RES INST
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202111352460.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-11-16
Publication Date
2024-12-13
Estimated Expiration
2041-11-16

AI Technical Summary

Technical Problem

In the prior art, under a low partial pressure carbon dioxide environment, the separation efficiency of carbon dioxide is low, making it difficult to effectively separate carbon dioxide from the mixture.

Method used

The LTA type zeolite molecular sieve material after exchange of sodium or potassium ions as a selective adsorbent, and its high responsiveness to carbon dioxide and barrier properties of other gases are used to achieve efficient selective adsorption and separation of carbon dioxide.

Benefits of technology

When the partial pressure of carbon dioxide is low, carbon dioxide can be efficiently separated from the mixture, with high separation efficiency, and the material is harmless to the human body, with simple preparation method and low cost, and has the potential for large-scale production and application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116135300B_ABST
    Figure CN116135300B_ABST
Patent Text Reader

Abstract

The present invention provides an adsorbent for selectively capturing CO2 and its preparation and application. The adsorbent is an LTA type zeolite molecular sieve material after sodium ion or potassium ion exchange. The adsorbent is prepared by uniformly mixing G, D2O, an aluminum source, a silicon source and water according to a molar ratio of G:D2O:Al2O3:SiO2 of 0-5:0.7-3:1:1-11, #imgabs0# of 25-60, and #imgabs1# of 0.1-2, reacting the mixed solution at 80-140°C, drying the obtained reaction product, and then subjecting the mixture to or not subjecting the mixture to calcination, and finally placing the dried product or the calcined product in a sodium chloride solution or a potassium chloride solution for ion exchange to obtain the adsorbent; D is potassium or sodium; and G is an organic template containing [(CH3)4N]2O or capable of forming [(CH3)4N]2O.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an adsorbent for selectively capturing CO2 and preparation and application thereof, belonging to the technical field of CO2 adsorption and separation. Background Art

[0002] Carbon dioxide is a common greenhouse gas, mainly derived from the combustion of fossil fuels such as oil, natural gas, and coal. These large amounts of carbon dioxide emissions can lead to an enhanced greenhouse effect and global warming, and trigger a series of natural disasters, such as increased pests and diseases, rising sea levels, abnormal climate, and land desertification. Therefore, reducing carbon dioxide emissions and separating and recycling them is a hot topic in the field of environmental protection.

[0003] Common carbon dioxide separation technologies include chemical absorption, physical adsorption, membrane separation and cryogenic distillation. Compared with other methods, the adsorption method has the advantages of simple process, low energy consumption, high degree of automation, and reversible adsorption, and is therefore widely used in the removal and capture of carbon dioxide in industry. Zeolite is a commonly used adsorbent. Due to its unique advantages such as high specific surface area and thermal stability, it has been industrially produced and applied in large quantities. Currently, commonly used zeolites include 4A, 5A, 13X, etc., which mainly use the characteristics of these zeolite adsorbents with different affinities for different components in the mixed gas for separation. The separation efficiency mainly depends on the selectivity of the zeolite adsorbent for different components. However, when the partial pressure of carbon dioxide in the mixed gas is low (such as in the flue gas after combustion, carbon dioxide accounts for only about 15%), the separation efficiency will be reduced. Therefore, the separation of low partial pressure carbon dioxide is still a major challenge.

[0004] In summary, providing a new type of adsorbent for selectively capturing CO2 and its preparation and application has become a technical problem that needs to be urgently solved in this field. Summary of the invention

[0005] In order to solve the above-mentioned shortcomings and deficiencies, an object of the present invention is to provide an adsorbent for selectively capturing CO2.

[0006] Another object of the present invention is to provide a method for preparing the above-mentioned adsorbent for selectively capturing CO2.

[0007] Another object of the present invention is to provide the use of the above-mentioned adsorbent for selectively capturing CO2 in separating carbon dioxide from a mixed gas.

[0008] Another object of the present invention is to provide a method for separating carbon dioxide from a mixed gas, wherein the method utilizes the above-mentioned adsorbent for selectively capturing CO2.

[0009] In order to achieve the above objectives, on the one hand, the present invention provides an adsorbent for selectively capturing CO2, wherein the adsorbent is an LTA type zeolite molecular sieve material after sodium ion or potassium ion exchange;

[0010] The adsorbent is first prepared according to the molar ratio of G:D2O:Al2O3:SiO2 of 0-5:0.7-3:1:1-11, 25 to 60, The reaction mixture is 0.1-2, G, D2O, aluminum source, silicon source and water are uniformly mixed, and then the obtained mixture is reacted at 80-140°C, and the obtained reaction product is dried, and then calcined or not, and finally the dried product or the calcined product is placed in a sodium chloride solution or a potassium chloride solution for ion exchange to obtain the product;

[0011] Wherein, D is potassium or sodium;

[0012] G is an organic template containing [(CH3)4N]2O or capable of forming [(CH3)4N]2O.

[0013] As a specific embodiment of the above-mentioned adsorbent of the present invention, the silicon-aluminum ratio of the LTA type zeolite molecular sieve material after sodium ion or potassium ion exchange is 1-7.

[0014] As a specific embodiment of the above adsorbent of the present invention, wherein the molar ratio of G:D2O:Al2O3:SiO2 is 0.1-5:0.7-3:1:1-11, 25 to 60, Mix G, D2O, aluminum source, silicon source and water evenly with a concentration of 0.1-2.

[0015] As a specific embodiment of the above adsorbent of the present invention, the organic template includes tetramethylammonium hydroxide. When the organic template is tetramethylammonium hydroxide, the [(CH3)4N]2O is a polymer formed by tetramethylammonium hydroxide.

[0016] As a specific embodiment of the above adsorbent of the present invention, wherein the drying temperature is 60-80°C.

[0017] As a specific embodiment of the above adsorbent of the present invention, wherein the calcination is carried out in air or inert atmosphere, and the calcination temperature is 350-650°C.

[0018] Wherein, when the raw materials used to prepare the adsorbent include organic template C4H 13When NO (tetramethylammonium hydroxide, TMAOH) is used, the product obtained after drying needs to be calcined at high temperature in air or inert atmosphere to remove the template during the preparation process. In some embodiments of the present invention, the inert atmosphere can be, for example, a nitrogen atmosphere.

[0019] On the other hand, the present invention also provides a method for preparing the above-mentioned adsorbent for selectively capturing CO2, wherein the method comprises:

[0020] (1) The molar ratio of G:D2O:Al2O3:SiO2 is 0-5:0.7-3:1:1-11, 25 to 60, The mixture is 0.1 to 2, and G, D2O, an aluminum source, a silicon source and water are uniformly mixed to obtain a mixed solution; wherein D is potassium or sodium, and G is an organic template containing [(CH3)4N]2O or capable of forming [(CH3)4N]2O;

[0021] (2) heating the mixed solution to 80-140° C. and reacting at this temperature, and centrifuging or filtering the resulting suspension after the reaction is completed;

[0022] (3) drying the solid product obtained after centrifugation or suction filtration to obtain an intermediate product;

[0023] (4) placing the intermediate product or the calcined intermediate product in a sodium chloride solution or a potassium chloride solution for ion exchange, and then washing, drying and grinding the obtained product to obtain the adsorbent for selectively capturing CO2, i.e., the sodium-type or potassium-type cationic zeolite molecular sieve.

[0024] In the present invention, although grinding is performed when preparing the adsorbent for selectively capturing CO2, the present invention does not make specific requirements on the specific mesh size of the adsorbent for selectively capturing CO2. Those skilled in the art can reasonably determine the mesh size of the adsorbent for selectively capturing CO2 according to actual on-site operation needs, as long as it is ensured that the purpose of the present invention can be achieved.

[0025] In another aspect, the present invention also provides the use of the above-mentioned adsorbent for selectively capturing CO2 in separating carbon dioxide from a mixed gas.

[0026] As a specific implementation of the above application of the present invention, the mixed gas is flue gas (flue gas) or biogas.

[0027] As a specific implementation of the above application of the present invention, the mixed gas includes carbon dioxide and nitrogen and / or methane.

[0028] As a specific embodiment of the above application of the present invention, the volume percentage of carbon dioxide in the mixed gas is not more than 15%. That is, when the partial pressure of carbon dioxide in the mixed gas is very low, the adsorbent provided by the present invention can still efficiently separate carbon dioxide from the mixed gas.

[0029] In yet another aspect, the present invention also provides a method for separating carbon dioxide from a mixed gas, wherein the method utilizes the above-mentioned adsorbent for selectively capturing CO2.

[0030] The present invention obtains LTA type zeolite molecular sieve material after sodium ion or potassium ion exchange by regulating the cation type of zeolite molecular sieve. Different from the mechanism of action of traditional adsorbents, the mechanism of gas separation provided by the adsorbent provided by the present invention is based on controllable screening. Specifically, when the zeolite molecular sieve material is used as a CO2 adsorbent to separate carbon dioxide from a mixed gas, the potassium ions or sodium ions in the zeolite molecular sieve material only respond to carbon dioxide gas, that is, potassium ions or sodium ions only allow specific carbon dioxide molecules to pass through and be adsorbed, while other types of gases (such as nitrogen and / or methane) cannot pass through and are blocked, thereby achieving efficient selective adsorption separation and purification of carbon dioxide, that is, high separation efficiency of carbon dioxide; and the LTA type zeolite molecular sieve material after sodium ion or potassium ion exchange is non-toxic and harmless to the human body, the preparation method is simple and easy, the cost is low, the gas separation performance is excellent, and it has the potential for large-scale production and application, and can be used for the separation and purification of mixed gases of multiple components. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0032] Figure 1 This is the XRD spectrum of the LTA zeolite molecular sieve material after potassium ion exchange obtained in Example 10 of the present invention.

[0033] Figure 2 This is a schematic diagram of the location of potassium ions in the LTA zeolite molecular sieve material after potassium ion exchange obtained in Example 10 of the present invention.

[0034] Figure 3 This is a graph showing the X-ray energy spectrum test results of the LTA zeolite molecular sieve material after potassium ion exchange obtained in Example 10 of the present invention.

[0035] Figure 4It is the adsorption isotherm (-196° C.) of nitrogen on the LTA zeolite molecular sieve material after potassium ion exchange obtained in Example 10 of the present invention.

[0036] Figure 5a It is the adsorption isotherm (0°C, 25°C, 50°C, 80°C) of carbon dioxide on the LTA zeolite molecular sieve material after potassium ion exchange obtained in Example 10 of the present invention.

[0037] Figure 5b It is the adsorption isotherm of nitrogen on the LTA zeolite molecular sieve material after potassium ion exchange obtained in Example 10 of the present invention (0°C, 25°C, 50°C, 80°C).

[0038] Figure 6 This is a schematic diagram of the theoretical selectivity results of the LTA zeolite molecular sieve material after potassium ion exchange prepared in Example 10 of the present invention to carbon dioxide and nitrogen in simulated post-combustion flue gas (CO2 / N2:15 / 85).

[0039] Figure 7 It is the adsorption isotherm (25° C.) of methane on the LTA zeolite molecular sieve material after potassium ion exchange obtained in Example 10 of the present invention.

[0040] Figure 8 This is a schematic diagram of the theoretical selectivity results of the LTA zeolite molecular sieve material after potassium ion exchange prepared in Example 10 of the present invention to carbon dioxide and methane in simulated natural gas (CO2 / CH4:50 / 50). DETAILED DESCRIPTION

[0041] "Range" disclosed herein is given in the form of lower limit and upper limit. It can be one or more lower limits, and one or more upper limits respectively. A given range is defined by selecting a lower limit and an upper limit. The selected lower limit and upper limit define the boundaries of a particular range. All ranges defined in this way are combinable, i.e. any lower limit can be combined with any upper limit to form a range. For example, for a particular parameter, a range of 60-120 and 80-110 is listed, and it is understood that a range of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​listed are 1 and 2, and the maximum range values ​​listed are 3, 4 and 5, then the following ranges can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5.

[0042] In the present invention, unless otherwise specified, the numerical range "ab" represents an abbreviation of any real number combination between a and b, where a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" have been listed in this document, and "0-5" is just an abbreviation of these numerical combinations.

[0043] In the present invention, unless otherwise specified, all embodiments and preferred embodiments mentioned herein can be combined with each other to form a new technical solution.

[0044] In the present invention, unless otherwise specified, all technical features and preferred features mentioned herein can be combined with each other to form a new technical solution.

[0045] In the present invention, unless otherwise specified, the term "including" mentioned herein may be open-ended or closed-ended. For example, the term "including" may mean that other materials and / or elements not listed may also be included, or may only include the listed materials and / or elements.

[0046] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical scheme of the present invention is now described in detail in conjunction with the following specific embodiments, but it should not be understood as limiting the applicable scope of the present invention.

[0047] Example 1

[0048] This embodiment provides an adsorbent for selectively capturing CO2, which is an LTA type zeolite molecular sieve material after potassium ion or sodium ion exchange, and the material is prepared by a preparation method comprising the following steps:

[0049] First, the corresponding raw materials such as silicon source, aluminum source, sodium source, organic template and water are uniformly mixed according to the molar ratio of SiO2:Al2O3:TMAOH:Na2O:H2O of 10:1.7:7.8:2:330; specifically, 1.9 g of sodium aluminate (which serves as both an aluminum source and a sodium source) is dissolved in 17.8 g of deionized water and stirred at room temperature for 1 h, and then 9 g of LUDOX AS-40 (which serves as a silicon source, wherein the content of SiO2 is 40 wt.%) and 17.1 g of tetramethylammonium hydroxide are added, and then the mixture is rapidly stirred at room temperature for 24 h to obtain a uniform mixture;

[0050] Then, the mixture was transferred to a 100 mL Teflon-lined stainless steel autoclave and heated to 40°C for 24 h, then the temperature was raised to 100°C and maintained for 28 h. After the reaction was completed, the resulting suspension was centrifuged, washed, dried (60-80°C), and ground to obtain an intermediate product.

[0051] The obtained intermediate product was then calcined at 600°C for 10 h in an air atmosphere to remove the organic template;

[0052] Finally, the calcined product is divided into two parts and placed in a 1M NaCl solution and a 1M KCl solution for ion exchange, respectively. The ion-exchanged samples are then washed, dried, and ground to obtain LTA zeolite molecular sieve materials after sodium ion or potassium ion exchange, i.e., the adsorbent for selectively capturing CO2.

[0053] Example 2

[0054] This embodiment provides an adsorbent for selectively capturing CO2, which is an LTA type zeolite molecular sieve material after potassium ion or sodium ion exchange, and the material is prepared by a preparation method comprising the following steps:

[0055] First, the corresponding raw materials such as silicon source, aluminum source, sodium source and water are uniformly mixed according to the molar ratio of SiO2:Al2O3:Na2O:H2O of 18:3.9:5:173; specifically, 6.1 g of sodium aluminate and 3.9 g of sodium hydroxide are dissolved in 30 mL of deionized water, and stirred at room temperature for 1 h, and then 25.9 g of LUDOX AS-40 (as a silicon source, wherein the content of SiO2 is 40 wt.%) is slowly added and stirred for 24 h to obtain a uniform mixture;

[0056] The mixture was then transferred to a 100 mL Teflon-lined stainless steel autoclave and heated to 90° C. for 24 h. After the reaction was completed, the resulting suspension was centrifuged, washed, dried (60-80° C.), and ground to obtain an intermediate product.

[0057] Finally, the intermediate product is divided into two parts and placed in a 1M NaCl solution and a 1M KCl solution for ion exchange respectively. The ion-exchanged samples are then washed, dried, and ground to obtain LTA zeolite molecular sieve materials after sodium ion or potassium ion exchange, i.e., the adsorbent for selectively capturing CO2.

[0058] Example 3

[0059] This embodiment provides an adsorbent for selectively capturing CO2, which is an LTA type zeolite molecular sieve material after potassium ion or sodium ion exchange, and the material is prepared by a preparation method comprising the following steps:

[0060] First, the corresponding raw materials such as silicon source, aluminum source, sodium source and water are uniformly mixed according to the molar ratio of SiO2:Al2O3:Na2O:H2O of 1.9:1:3:128; specifically, two solutions, solution A and solution B, are prepared respectively, solution A: sodium aluminate and sodium hydroxide are dissolved in deionized water, and the solution is vigorously stirred until it is clear, solution B: sodium silicate and sodium hydroxide are dissolved in deionized water, and the solution is stirred until it is clear, solution B is poured into solution A, mixed evenly, and a mixed solution is obtained;

[0061] The mixed solution is then transferred to a stainless steel high-pressure reactor with a Teflon liner, and the reactor is placed in an oven at 100° C. and heated for 4 hours. After the reaction is completed, the obtained suspension is centrifuged, washed, dried (60-80° C.), and ground to obtain an intermediate product;

[0062] Finally, the intermediate product is divided into two parts and placed in a 1M NaCl solution and a 1M KCl solution for ion exchange respectively. The ion-exchanged samples are then washed, dried, and ground to obtain LTA zeolite molecular sieve materials after sodium ion or potassium ion exchange, i.e., the adsorbent for selectively capturing CO2.

[0063] Example 4

[0064] This embodiment provides an adsorbent for selectively capturing CO2, which is an LTA type zeolite molecular sieve material after potassium ion or sodium ion exchange, and the material is prepared by a preparation method comprising the following steps:

[0065] First, 490g of tetraethyl orthosilicate, 87.5g of sodium hydroxide and 530g of sodium aluminate were dissolved in 1880mL of deionized water, and then the resulting mixture was distilled for 1.5 to 2h, with a starting temperature of 100°C and an end temperature of 83°C. The reaction equation occurring during the reaction is as follows:

[0066] NaAlO2+x(C2H5O)4Si+2xH2O→Na(AlO2·xSiO2)+4xC2H5OH;

[0067] After the reaction is completed, the product is centrifuged, washed, dried, and ground to obtain a solid product, which is amorphous sodium aluminosilicate, and the composition (mass ratio) is: 17.7SiO2: 17.5Al2O3: 10.7Na2O: 45.8H2O;

[0068] Next, 8.2 mL of silica gel (LUDOX, model Sigma-Aldrich, each mL of silica gel contains 0.31 g of SiO2) was dissolved in 36 mL (concentration 2.4 mol / L) of tetramethylammonium hydroxide solution and stirred evenly, and then 10 g of the amorphous sodium aluminosilicate prepared above (as silicon source, aluminum source and sodium source) was added, and the resulting mixture was transferred to a 100 mL Teflon-lined stainless steel autoclave, and heated to 120-130° C., and stirred continuously for 72 h. After the reaction was completed, the product was centrifuged, washed, dried (60-80° C.), and ground to obtain an intermediate product;

[0069] The obtained intermediate product was then calcined at 600°C for 10 h in an air atmosphere to remove the organic template;

[0070] Finally, the calcined product is divided into two parts and placed in a 1M NaCl solution and a 1M KCl solution for ion exchange, respectively. The ion-exchanged samples are then washed, dried, and ground to obtain LTA zeolite molecular sieve materials after sodium ion or potassium ion exchange, i.e., the adsorbent for selectively capturing CO2.

[0071] Example 5

[0072] This embodiment provides an adsorbent for selectively capturing CO2, which is an LTA type zeolite molecular sieve material after potassium ion or sodium ion exchange, and the material is prepared by a preparation method comprising the following steps:

[0073] First, two solutions, solution A and solution B, were prepared respectively. Solution A: 21.5 g of sodium aluminate was dissolved in 250 mL of deionized water; solution B: 20.25 g of silica gel was dissolved in 285 mL of a 2.49 mol / L tetramethylammonium hydroxide solution at 100° C., solutions A and B were heated to boiling respectively, and solution B was quickly poured into solution A under stirring conditions, and stirring was continued for 2 minutes to obtain a mixed solution. In the obtained mixed solution, the molar ratio of SiO2 to Al2O3 was 3.9:1;

[0074] Then, the obtained mixed solution was transferred to a Teflon-lined stainless steel autoclave and heated to 100°C for 24 hours. After the reaction was completed, the obtained suspension was centrifuged, washed, dried (60-80°C), and ground to obtain an intermediate product.

[0075] The obtained intermediate product was then calcined at 350°C for 10 h under a nitrogen atmosphere to remove the organic template;

[0076] Finally, the calcined product is divided into two parts and placed in a 1M NaCl solution and a 1M KCl solution for ion exchange, respectively. The ion-exchanged samples are then washed, dried, and ground to obtain LTA zeolite molecular sieve materials after sodium ion or potassium ion exchange, i.e., the adsorbent for selectively capturing CO2.

[0077] Example 6

[0078] This embodiment provides an adsorbent for selectively capturing CO2, which is an LTA type zeolite molecular sieve material after potassium ion or sodium ion exchange, and the material is prepared by a preparation method comprising the following steps:

[0079] First, two solutions, solution A and solution B, are prepared respectively. Solution A: 4.3 g of sodium aluminate is dissolved in 50 mL of deionized water; solution B: 4.05 g of silica gel is dissolved in 50 mL of 2.7 mol / L tetramethylammonium hydroxide solution; under rapid stirring conditions, solution B is quickly poured into solution A, and the molar ratio of SiO2 to Al2O3 in the obtained mixed solution is 4:1), and distillation (temperature is 120-130° C.) is carried out for two days. During the distillation reaction, the mixed solution is continuously stirred until a solid product is formed. After the reaction is completed, the product is centrifuged, washed, dried (60-80° C.), and ground to obtain an intermediate product;

[0080] The obtained intermediate product was then calcined at 350°C for 10 h under a nitrogen atmosphere to remove the organic template;

[0081] Finally, the calcined product is divided into two parts and placed in a 1M NaCl solution and a 1M KCl solution for ion exchange, respectively. The ion-exchanged samples are then washed, dried, and ground to obtain LTA zeolite molecular sieve materials after sodium ion or potassium ion exchange, i.e., the adsorbent for selectively capturing CO2.

[0082] Example 7

[0083] This embodiment provides an adsorbent for selectively capturing CO2, which is an LTA type zeolite molecular sieve material after potassium ion or sodium ion exchange, and the material is prepared by a preparation method comprising the following steps:

[0084] First, referring to the preparation method provided in Example 4, amorphous sodium aluminosilicate is prepared using an appropriate amount of raw materials such as ethyl orthosilicate and sodium aluminate. In this embodiment, drying treatment is required before obtaining the amorphous sodium aluminosilicate product to remove the water contained therein. The composition (molar ratio) of the finally obtained amorphous sodium aluminosilicate is: 82SiO2:8.4Al2O3:9.7Na2O;

[0085] Then, 10 g of the amorphous sodium aluminosilicate prepared above (as a silicon source, an aluminum source and a sodium source) and 0.2 g of ZK-4 zeolite (a conventional material, commercially available or homemade, which serves as both a silicon source and an aluminum source) were added to 55 mL of a 2.6 mol / L tetramethylammonium hydroxide solution, and distilled (120-130° C.) for 13.5 h. After the reaction was completed, the product was centrifuged, washed, dried (60-80° C.), and ground to obtain an intermediate product;

[0086] The obtained intermediate product was then calcined at 350°C for 10 h under a nitrogen atmosphere to remove the organic template;

[0087] Finally, the calcined product is divided into two parts and placed in a 1M NaCl solution and a 1M KCl solution for ion exchange, respectively. The ion-exchanged samples are then washed, dried, and ground to obtain LTA zeolite molecular sieve materials after sodium ion or potassium ion exchange, i.e., the adsorbent for selectively capturing CO2.

[0088] Example 8

[0089] This embodiment provides an adsorbent for selectively capturing CO2, which is an LTA type zeolite molecular sieve material after potassium ion or sodium ion exchange, and the material is prepared by a preparation method comprising the following steps:

[0090] First, 100 g of the amorphous sodium aluminosilicate prepared in Example 7 (as a silicon source, an aluminum source and a sodium source) was mixed with 2 g of ZK-4 zeolite (as both a silicon source and an aluminum source), and the resulting mixture was added to 550 mL of a 2.65 mol / L tetramethylammonium hydroxide solution, and distilled (120-130° C.) for 17 h. After the reaction was completed, the product was centrifuged, washed, dried (60-80° C.), and ground to obtain an intermediate product;

[0091] The obtained intermediate product was then calcined at 350°C for 10 h in an air atmosphere to remove the organic template;

[0092] Finally, the calcined product is divided into two parts and placed in a 1M NaCl solution and a 1M KCl solution for ion exchange, respectively. The ion-exchanged samples are then washed, dried, and ground to obtain LTA zeolite molecular sieve materials after sodium ion or potassium ion exchange, i.e., the adsorbent for selectively capturing CO2.

[0093] Example 9

[0094] This embodiment provides an adsorbent for selectively capturing CO2, which is an LTA type zeolite molecular sieve material after potassium ion or sodium ion exchange, and the material is prepared by a preparation method comprising the following steps:

[0095] First, 0.3 g of ZK-4 zeolite (as both a silicon source and an aluminum source) was added to 10 mL of deionized water containing 3.45 g of sodium aluminate and stirred evenly. Under stirring conditions, 36.75 g of tetramethylammonium hydroxide and 59 mL of a 2.47 mol / L tetramethylammonium hydroxide solution were added. When a large amount of precipitate was formed, stirring was stopped, and the oil bath was heated to 100° C. and maintained for 39 hours. After the reaction was completed, the product was centrifuged, washed, dried, and ground to obtain an intermediate product.

[0096] The obtained intermediate product was then calcined at 350°C for 10 h in an air atmosphere to remove the organic template;

[0097] Finally, the calcined product is divided into two parts and placed in a 1M NaCl solution and a 1M KCl solution for ion exchange, respectively. The ion-exchanged samples are then washed, dried, and ground to obtain LTA zeolite molecular sieve materials after sodium ion or potassium ion exchange, i.e., the adsorbent for selectively capturing CO2.

[0098] Example 10

[0099] This embodiment provides an adsorbent for selectively capturing CO2, which is an LTA type zeolite molecular sieve material after potassium ion or sodium ion exchange, and the material is prepared by a preparation method comprising the following steps:

[0100] (1) 3.06 g of sodium aluminate and 1.95 g of sodium hydroxide were dissolved in deionized water and stirred at room temperature for 1 h, and then 12.95 g of LUDOX AS-40 silica gel (as a silicon source, wherein the SiO2 content is 40 wt.%) and 15 mL of deionized water were added, and the resulting solution was aged at room temperature for 24 h;

[0101] (2) The solution obtained in step (1) was transferred to a 50 mL stainless steel autoclave with a polytetrafluoroethylene liner and heated at 90° C. for 1 d; the obtained white product was then centrifuged, washed, dried, and ground;

[0102] (3) The white product obtained in step (2) is divided into two parts, and placed in a 1 mol / L NaCl solution and a 1 mol / L potassium chloride solution for ion exchange at room temperature and a magnetic stirring rate of 350 r / min. The ion-exchanged sample is washed, dried, and ground to obtain an LTA zeolite molecular sieve material after sodium ion or potassium ion exchange, i.e., the adsorbent for selectively capturing CO2.

[0103] Test Example 1

[0104] XRD analysis was performed on the LTA zeolite molecular sieve material obtained in Example 10 after potassium ion exchange. The obtained XRD pattern is as follows: Figure 1 As shown, the Rietveld structure refinement results reveal that the potassium ion is located at the center of the eight-membered ring of the LTA zeolite molecular sieve material ( Figure 2 ), which shows that the material has the potential to become a trapdoor adsorbent.

[0105] The LTA zeolite molecular sieve material obtained in Example 10 after potassium ion exchange was subjected to X-ray spectrum test. The test results showed that the silicon-aluminum ratio of the material was 2.45 (eg Figure 3 shown).

[0106] At a temperature of -196°C, the adsorption isotherm of nitrogen on the LTA zeolite molecular sieve material after potassium ion exchange obtained in Example 10 was measured. The results are as follows: Figure 4 As shown, from Figure 4 It can be seen that the nitrogen adsorption amount of the material at -196°C is very low, indicating that nitrogen cannot diffuse into the pores of the material at this temperature, and thus exhibits characteristics similar to those of non-porous materials to nitrogen.

[0107] Test Example 2

[0108] 0.15 g of the LTA zeolite molecular sieve material after potassium ion exchange obtained in Example 10 was degassed in a vacuum atmosphere (350° C.) for 10 h. After the temperature dropped to room temperature, isothermal adsorption tests of carbon dioxide and nitrogen were performed (the temperatures were 0° C., 25° C., 50° C., and 80° C., respectively). The adsorption isotherms of carbon dioxide and nitrogen on the LTA zeolite molecular sieve material after potassium ion exchange obtained in Example 10 (0° C., 25° C., 50° C., and 80° C.) were as follows: Figure 5a and Figure 5b As shown. Figure 5a and Figure 5bIt can be seen that carbon dioxide has an objective adsorption amount at the measured temperature, indicating that the material can respond to carbon dioxide, thereby allowing carbon dioxide to diffuse into its pores; on the contrary, nitrogen shows almost no adsorption at the measured temperature, indicating that nitrogen cannot diffuse into the pores of the material. This result shows that: within the measured temperature range, the material can selectively adsorb carbon dioxide.

[0109] Therefore, the theoretical selectivity of carbon dioxide and nitrogen in the simulated flue gas (wherein the volume percentages of CO2 and N2 are 15% and 85%, respectively) was tested using the LTA zeolite molecular sieve material after potassium ion exchange prepared in Example 10. The test results are as follows: Figure 6 As shown. Figure 6 It can be seen that the material exhibits very excellent carbon dioxide / nitrogen selectivity. Specifically, at a temperature of 50°C, the carbon dioxide / nitrogen selectivity is as high as nearly 600.

[0110] The calculation formula of carbon dioxide / nitrogen selectivity is shown in the following formula 1):

[0111]

[0112] In formula 1), S is the selectivity of carbon dioxide / nitrogen, P is the partial pressure of the gas component in the mixed gas, and Q is the adsorption amount of the gas under pressure P.

[0113] Test Example 3

[0114] 0.15 g of the LTA zeolite molecular sieve material obtained in Example 10 after potassium ion exchange was degassed in a vacuum atmosphere (350° C.) for 10 h, and after the temperature dropped to room temperature, a methane isotherm adsorption test (25° C.) was performed. The adsorption isotherm (25° C.) of methane on the LTA zeolite molecular sieve material obtained in Example 10 of the present invention after potassium ion exchange is as follows: Figure 7 As shown. Figure 7 It can be seen that methane shows almost no adsorption at the measured temperature, which indicates that methane cannot diffuse into the pores of the material. This result further shows that: within the measured temperature range, the material shows very excellent carbon dioxide / methane selectivity and can be used for the separation and purification of biogas.

[0115] Therefore, the theoretical selectivity of carbon dioxide and methane in simulated natural gas (wherein the volume percentage of CO2 and CH4 is 50%) was tested using the LTA zeolite molecular sieve material after potassium ion exchange prepared in Example 10. The test results are as follows: Figure 8 As shown. Figure 8It can be seen that the material exhibits very excellent carbon dioxide / methane selectivity. Specifically, at a temperature of 25°C, the carbon dioxide / methane selectivity can reach 71.

[0116] The calculation formula of carbon dioxide / methane selectivity is shown in the following formula 2):

[0117]

[0118] In formula 2), S1 is the selectivity of carbon dioxide / methane, P is the partial pressure of the gas component in the mixed gas, and Q is the adsorption amount of the gas under pressure P.

[0119] The potassium ion LTA zeolite provided in the embodiment of the present invention, that is, the potassium ions in the LTA zeolite molecular sieve material after potassium ion exchange, have selective permeability to different gas molecules. Therefore, it can be used as a highly selective carbon dioxide adsorbent, providing a feasible and easy-to-implement method for capturing low partial pressure carbon dioxide gas in a mixed gas.

[0120] The above is only a specific embodiment of the present invention, and cannot be used to limit the scope of the invention. Therefore, the replacement of equivalent components, or equivalent changes and modifications made according to the protection scope of the patent of the present invention, should still fall within the scope of this patent. In addition, the technical features of the present invention can be freely combined with each other, with each other and with each other, and with each other.

Claims

1. A selective capture of CO 2 The adsorbent It is characterized in that The adsorbent is an LTA type zeolite molecular sieve material after potassium ion exchange; The adsorbent is firstly prepared according to G:D 2 O:Al 2 O 3 :SiO 2 The molar ratio is 0-5:0.7-3:1:1-11, 25 to 60, G and D are 0.1 to 2 2 O, aluminum source, silicon source and water are mixed evenly, and then the obtained mixed solution is reacted at 80-140° C., the obtained reaction product is dried, and then calcined or not, and finally the dried product or the calcined product is placed in a potassium chloride solution for ion exchange to obtain the product; Wherein, D is potassium or sodium; G is a compound containing [(CH 3 ) 4 N] 2 O or can form [(CH 3 ) 4 N] 2 O organic template.

2. The adsorbent according to claim 1, It is characterized in that The silicon-aluminum ratio of the LTA type zeolite molecular sieve material after potassium ion exchange is 1-7.

3. The adsorbent according to claim 1, It is characterized in that Press G:D 2 O:Al 2 O 3 :SiO 2 The molar ratio is 0.1-5:0.7-3:1:1-11, 25 to 60, G and D are 0.1 to 2 2 O, aluminum source, silicon source and water are mixed evenly.

4. The adsorbent according to any one of claims 1 to 3, It is characterized in that The organic template includes tetramethylammonium hydroxide.

5. The adsorbent according to any one of claims 1 to 3, It is characterized in that The drying temperature is 60-80°C.

6. The adsorbent according to any one of claims 1 to 3, It is characterized in that The calcination is carried out in air or inert atmosphere at a temperature of 350-650°C.

7. The selective capture of CO according to any one of claims 1 to 6 2 A method for preparing an adsorbent, It is characterized in that The method comprises: (1) Press G:D 2 O:Al 2 O 3 :SiO 2 The molar ratio is 0-5:0.7-3:1:1-11, 25 to 60, G and D are 0.1 to 2 2 O, aluminum source, silicon source and water are mixed evenly to obtain a mixed solution; wherein D is potassium or sodium, G is a 3 ) 4 N] 2 O or can form [(CH 3 ) 4 N] 2 O organic template; (2) heating the mixed solution to 80-140° C. and reacting at this temperature, and centrifuging or filtering the resulting suspension after the reaction is completed; (3) drying the solid product obtained after centrifugation or suction filtration to obtain an intermediate product; (4) placing the intermediate product or the intermediate product after calcination in a potassium chloride solution for ion exchange, and then washing, drying and grinding the obtained product to obtain the selective capture of CO 2 of adsorbent.

8. The selective capture of CO according to any one of claims 1 to 6 2 Application of adsorbents in separating carbon dioxide from mixed gases.

9. The use according to claim 8, It is characterized in that The mixed gas is flue gas or biogas.

10. The use according to claim 8, It is characterized in that The mixed gas includes carbon dioxide and nitrogen and / or methane.

11. The use according to any one of claims 8 to 10, It is characterized in that The volume percentage of carbon dioxide in the mixed gas is not more than 15%.

12. A method for separating carbon dioxide from a mixed gas, It is characterized in that The method uses the selective capture of CO according to any one of claims 1 to 6 2 of adsorbent.